Differential efficacies of human type I and type II interferons as antiviral and antiproliferative agents. - Rubin, B Y (1980)
Treatment of human fibroblast FS-4 cultures with human type II interferon preparations induced the synthesis of at least four proteins that were similar in size to four of the five proteins induced by type I interferons (Mr 120,000, 88,000, 67,000, and 56,000). However, the Mr 67,000 and 56,000 proteins were induced more strongly by type II than by type I interferon, and a counterpart of a Mr 80,000 protein induced by type I interferons was not noticeably induced by type II interferon preparations. We therefore compared type I and type II interferons for relative antiviral activities against different viruses (vesicular stomatitis, encephalomyocarditis, and vaccinia viruses and reovirus) and for cell growth-inhibitory activities on various cell types. The replication of vesicular stomatitis and encephalomyocarditis viruses was inhibited more strongly by type I interferon, whereas reovirus and vaccinia virus showed greater sensitivity to type II interferon preparations. This indicates that viruses may differ in their sensitivity to human type I and type II interferons and that the antiviral mechanisms induced by type I and type II interferons may have significant differences. The type I and type II interferons may have significant differences. The type I and type II interferons may also differ in their efficacies as antiproliferative agents. Type II interferon preparations at 2.5 units/ml inhibited the incorporatin of [3H]thymidine to a greater extent than did type I interferon at 400 units/ml. (For both type I and type II interferons, the unit of interferon activity was defined as the concentration that decreased the yield of vesicular stomatitis virus by 50% in FS-4 cultures.) Furthermore, whereas type II interferon preparations had a reversible cytostatic effect on normal human fibroblasts at 10 units/ml, the transformed cells tested (HeLa, osteosarcoma, U-amnion) showed extensive cell death, thus indicating that it may have a cytocidal effect on certain tumor cells. It appears that human type II interferon (or a factor present in these preparations) may be a potent antitumor agent.